Slovenski podjetniški observatorij 2000 = Slovene entrepreneurship observatory 2000 - Rebernik, Miroslav; Močnik, Dijana; Rus, Matej (University of Maribor Press, 2000)
Slovene entrepreneurship observatory 2000. The importance of small and medium sized enterprises is very big, and there are ever more of these enterprises on a European and global scale, with the increasing number of people employed in them. There is also no doubt that the importance of small and medium sized enterprises will further increase, not least because of the widespread use of the internet, the borders of enterprises are changing, and the development of technology, globalisation of business and general reduction of transaction costs contribute to small and medium enterprises which are becoming increasingly competitive. In line with the growing importance of small and medium enterprises is also the growing need for regular monitoring of their development and for comparison between countries. Slovenian Entrepreneurship Observatory is the first publication of this kind in Slovenia, which is entirely devoted to the study of this phenomenon. The first part presents an analysis of Slovenian companies for the year 1999 by regions, industries and size classes. In the second part, we compare the Slovenian economy with the European economy. In the third part, we discuss some of the more important results of the field research carried out among Slovene enterprises.